Effects of different levels of irrigation suppression and fertigation on potato yield - Jonathan dos Santos; Palaretti, Luiz Fabiano; Faria, Rogério Teixeira de; Silva, Wilson Araújo da; Silva, Cristiane Matos da; Sousa, Patrícia Ferreira Cunha; Sousa , Thatyane Pereira de; Dalri , Alexandre Barcellos (Comunicata Scientiae, 2024)
With the limitation in the availability of water for agriculture and the high costs of fertilizers, it is necessary to adopt strategies for water and nutritional management of agricultural crops. The objective of this study was to evaluate the morphological and physiological characteristics and productivity of potato under the influence of suppression of irrigation and fertigation in Jaboticabal, SP, Brazil. The experiment was carried out in randomized blocks, conducted in the field, using a 3 x 2 factorial scheme. Different times of irrigation suppression were studied at 80, 90 and 100 days after planting, along with forms of fertigation, following the rate of crop absorption and equivalent fertigation. The imposition of irrigation suppression at 100 days, linked to fertigation following the rate of crop absorption, showed a positive effect on the aerial fresh mass of the potato variety studied, especially promoting the increase in productivity, which was 47.82 t ha-1, and efficiency in water use, which was 10.53 kg of tubers per cubic meter of water. This observation indicates that the application of fertilizers, in sync with the needs of the crop, can improve the efficiency of water use and increase productivity. These findings highlight the importance of integrated strategies to optimize potato cultivation and make it more resistant to adversity, seeking a more sustainable and productive agriculture.